CFSP – Vacillating Between Supranationalism and Intergovernmentalism? - Ligia Corduneanu (CES Working Papers, 2014)
The Common Foreign and Security Policy (CFSP) of the European Union (EU) faces an identity crisis to which the member states do not seem eager to put an end. Making incremental changes without defining the objectives will not rise the trust in the EU as a strong international actor. Thus, this paper aims to indicate the supranational and intergovernmental characteristics of the CFSP in order to highlight that the neofonctionalist model of governance has also shaped a policy area believed to belong exclusively to the member states' power. The paper analyses the supranational and intergovernmental dimensions of the CFSP in order to provide a better understanding of how this policy is constructed.
Keywords: Y80; 330; Common and Foreign Security Policy; intergovernamentalism; supranationalism; multi-level governance